Methodological aspects and results of the baseline of the monitoring of health in adults and elderly infected by Sars-Cov-2 (Sulcovid-19) (Revista Contexto & Saúde, 2024)
AIM: To describe the methodology and sample used in the study, as well as the prevalence of symptoms during the acute phase of infection according to socioeconomic variables. METHODS: A cross-sectional study conducted in Rio Grande with individuals infected by SARS-CoV-2 from December 2020 to March 2021. Nineteen symptoms present during the acute phase of infection were investigated and analyzed separately and categorized as "0-4," "5-9," and "10 or more," according to sex, age, and economic class. RESULTS: 2,919 individuals were included in the sample. The most prevalent symptoms were fatigue (73.7%), headache (67.2%), loss of taste (65.9%), loss of smell (63.9%), and muscle pain (62.3%). Regarding the occurrence of symptoms stratified by sex, all symptoms except productive cough were statistically higher in females. Regarding age, it was found that headache, pain/discomfort breathing, loss of taste, loss of smell, fatigue, sore throat, nasal congestion, diarrhea, joint pain, and muscle pain were statistically higher among adults (18-59 years old). Regarding economic class, the prevalence of symptoms such as shortness of breath, pain/discomfort breathing, altered sensitivity, and joint pain increased linearly with decreasing economic class. CONCLUSION: The results of this study allowed identifying the most frequent symptoms during the acute phase of COVID-19 and their distribution among groups, providing data for the implementation of public policies by managers and support for healthcare professionals in assisting this population.
Keywords: COVID-19; SARS-CoV-2; Pandemics; Cross-Sectional Studies; Methods